PENGARUH TANGGUNG JAWAB LINGKUNGAN PERUSAHAAN (CER) TERHADAP KINERJA KEUANGAN PERUSAHAAN (CFP) : DENGAN PERATURAN PEMERINTAH DAN SLACK ORGANISASI SEBAGAI MODERASI - Susi Susanti; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2019)
This study aims to empirically examine the effect of corporate environmental responsibility (CER) on corporate financial performance (CFP) and the moderating effect of government regulations and organizational slack. This research is based on agency theory and institutional theory. The population in this study consisted of energy-intensive companies listed on the Indonesia Stock Exchange in 2014-2016. This study used a purposive sampling method, as many as 145 companies as the final sampling number. The company's environmental responsibility is measured by the GRI index which is composed of 8 points containing 38 items, while the company's financial performance uses the value of ROA one year later, namely 2015-2017. This study uses a multiple regression analysis model in testing hypotheses. The results of this study indicate that corporate environmental responsibility has a positive effect on the corporate financial performance. In addition, this study also shows that government regulations positively moderate the relationship between corporate environmental responsibility and corporate financial performance. Finally, the results of this study are organizational slack moderating the relationship between corporate environmental responsibility and corporate financial performance.